Serum Sclerostin as an Independent Marker of Peripheral Arterial Stiffness in Renal Transplantation Recipients: A Cross-Sectional Study. Issue 15 (April 2016) - Hsu, Bang-Gee; Liou, Hung-Hsiang; Lee, Chung-Jen; Chen, Yen-Cheng; Ho, Guan-Jin; Lee, Ming-Che
Abstract : Abstract: Wnt/β-catenin signaling pathway is thought to be implicated in the development of arterial stiffness and vascular calcification. As a Wnt signaling pathway inhibitor, it is interesting to investigate whether sclerostin or dickkopf-1 (DKK1) level is correlated with arterial stiffness in renal transplant (RT) recipients. Fasting blood samples were obtained for biochemical data, sclerostin, DKK1, and osteoprotegerin (OPG) determinations. In this study, we applied automatic pulse wave analyzer (VaSera VS-1000) to measure brachial-ankle pulse wave velocity and either sides of brachial-ankle pulse wave velocity value, which greater than 14.0 m/s was determined as high arterial stiffness. Among 68 RT recipients, 30 patients (44.1%) were in the high arterial stiffness group. Compared with patients in the low arterial stiffness group, patients in the high arterial stiffness group had higher prevalence of hypertension ( P = 0.002), diabetes ( P < 0.001), metabolic syndrome ( P = 0.025), longer posttransplant duration ( P = 0.005), higher systolic blood pressure ( P < 0.001) and diastolic blood pressure ( P = 0.018), and higher fasting glucose ( P = 0.004), total cholesterol ( P = 0.042), blood urea nitrogen ( P = 0.020), phosphorus ( P = 0.042), and sclerostin levels ( P = 0.001). According to our multivariable forward stepwise linear regression analysis, age ( β = 0.272, P = 0.014), phosphorus ( β = 0.308, P = 0.007), and logarithmically-transformed OPG (log-OPG; β = 0.222, P = 0.046) were positively associated with sclerostin levels, and multivariate logistic regression analysis, sclerostin (odds ratio 1.052, 95% confidence interval 1.007–1.099, P = 0.024), and posttransplant duration (odds ratio 1.024, 95% confidence interval 1.004–1.045, P = 0.019) were the independent predictors of peripheral arterial stiffness in RT recipients. In this study, serum sclerostin level, but not DKK1, was proved to be involved in the pathogenetic process of peripheral arterial stiffness in RT recipients.